Phytochemical Screening and Antibacterial Activity of Acorus calamus L. Extracts - Bayyinatul Muchtaromah; Alfiah Hayati; Erna Agustina (Jurnal Biodjati, 2019)
Staphylococcus aureus and Escherichia coli are among the most common species of gram-positive and gram-negative bacteria, which cause vaginitis, in infertile women. The Calamus rhizome (Acorus calamus L.) is an Indonesian plant that has antibacterial properties that can be used to treat vaginitis and increase fertility. The aim of this study was to determine the phytochemical and antibacterial activity of the calamus rhizoma in polar, semi-polar and non-polar solvents in the growth of S. aureus and E. coli. The antibacterial activity test was in the form of inhibitory test using the Kirby-Bauer, Minimum Inhibi-tion Concentration (MIC) and Minimum Bactericidal Concentration (MBC) by microdilution method with multilevel dilution (concentra-tions 50; 25; 12.5; 6.25; 3.13; 1.56; 0.78; and 0.39%). The screening results showed that ethanol and n-hexane extract contained alkaloids and triterpenoids, while chloroform extract was only triterpenoid. Chloroform extract produced the largest inhibition zone diameter of S. aureus and E. coli (7.26 and 3.28 mm), followed by ethanol extract (5.90 and 3.07 mm) and n-hexane extract (5.33 and 2.95 mm). The concentrations of 0.39 and 0.78% were the values of MIC and MBC for all three extracts, indicating that the extract of the calamus rhizome with several solvents in this study had the same antibacterial activity.